Colombia 2025 - Egerton, Alex; Watilo Blake, Laura; Garry, John; Gutierrez-Jones, Jackie; Rueda, Manuel (Travel writer) (Lonely Planet guidebooks., 2025)
Lonely Planet's local travel experts reveal all you need to know to plan the trip of a lifetime in this latest edition of our guide to Colombia. Discover Colombia's most popular experiences and best kept secrets from taking a boat trip with an Indigenous guide to spot pink river dolphins; to hiking for days through sultry thick jungle to emerge at the spectacular stone foundations of the Ciudad Perdida; and encountering total relaxation on the diminutive Caribbean islands of the Islas del Rosario.